Analisis Pengaruh Kepemilikan Institusional dan Kepemilikan Manajerial Terhadap Kinerja dan Nilai Perusahaan - Danies Rifky Akbar Darmawan Putra (Universitas Prasetiya Mulya, 2017)
Conflict of interest between shareholders and management can trigger the increase of cost production of the company and give an effect on the performance and value of the company. The purpose of this study is to examine the effect between ownership structures, the institutional and managerial ownership on the performance and the value of companies. Based on the sample of 193 non-financial companies listed in Indonesia’s Stocks Exchange for the period 2004 to 2015 by using purposive sampling method, institutional ownership gives a positive effect on the performance and value of the companies, while managerial ownership gives a negative effect on the performance as well as the value of the companies. Keywords: Institutional Ownership, Managerial Ownership, Company Performance, Company Value https://doi.org/10.21632/saki.1.1.1-24